METODE PENGHAPUSAN ASET BMN KONDISI RUSAK BERAT SEBAGAI NILAI PENDAPATAN KEKAYAAN NEGARA DI NAVIGASI TIPE B TANJUNG PRIOK - Erlina Erlina; Koerniawan Hidajat (LPPM Universitas Bina Bangsa, 2023)
State-owned goods (BMN) are all goods purchased or obtained at the expense of the State Revenue and Expenditure Budget or originating from other legitimate acquisitions. BMN with severely damaged conditions must be removed in order to create efficiency in its use. The purpose of this study was to determine the Analysis of the BMN Assets Lost Condition as a Value of State Wealth Revenue in Tanjung Priok Type B Navigation. This article uses a descriptive qualitative method. The results in this article reveal that the procedures carried out were appropriate even though they had experienced problems in the auction. This article has implications for the Tanjung Priok Type B Navigation District to better adjust the price estimate to the condition of the goods being auctioned.